Hipertexto no ensino fundamental II: estratégias de leitura - Mangili, Patrícia Alessandra (2011)
The importance of the internet is increasing in all human activities and in consequence, the process of organization and development of knowledge, as the forms of conceive and share experiences have been modified. In this context, it is school role, also in Portuguese classes, to assist students to build meanings in reading activities and production of different digital texts genres. It becomes essential, in our view, that teachers know their students practices, to later assist them to improve their reading competences on the contemporary society. We consider that these reading activities are fundamental to a meaningful learning, that ensure the students the development of the competencies that help them to overcome the present challenges. So, trying to know how students do the reading of the digital texts genres, we investigate, on this research, the paths went through and the strategies used by them during the hypertexts reading. On the theoretical point of view, the research is based on a sociocognitive-interactive perspective, having as guide, especially, Kato (1992), Kleiman (1995, 2002, 2008), Koch (2000, 2002, 2009), Marcuschi (1995, 1996, 2008), Solé (1998), and others. To the hypertext approach, we considered the studies of Koch (2007), Lévy (1993,1999 e 2003) Mcaleese (1993), Marcuschi (1999, 2000, 2004 and 2007), Santaella (2004), and others. It is an exploratory-descriptive research. The methodology was developed through out a questionnaire with 43 questions to identify the reading strategies used by 84 elementary students, from 8th and 9th grades, of a public school in Dois Córregos, São Paulo. The results indicate that most part of the individuals researched sets goals and define hypotheses during the reading of hypertext, among other strategies used; on the other hand, strategies such as organization of a reading script and establishment of generalizations are not constant on the reading practice and should be explored in the classroom, considering the need of improvement of the students reading competence in digital texts genres. As the reading of hypertext is a frequent practice among many students, we recognize and understand that the reading strategies they used must be a part of the teaching work, because only on this way we, teachers, will can develop a work concentrated in the formation of autonomous readers, able to understand any textual genre and comment about it. The results descriptions and the reflections that we present about them could be subsidies for future investigations that aim the development of hypertext reading strategies in pedagogical activities, which may represent an important aid to teaching work to educate readers that know the importance of appropriate strategies to various reading situations in the contemporary society, where virtual text the hypertext has played a very important role